Vibrational branching ratios and hyperfine structure of 11BH and its suitability for laser cooling - Hendricks, R. J.; Holland, D. A.; Truppe, S.; Sauer, B. E.; Tarbutt, M. R. (Frontiers in Physics, 2014)
The simple structure of the BH molecule makes it an excellent candidate for direct laser cooling. We measure the branching ratios for the decay of the A^{1}Pi (v'=0) state to vibrational levels of the ground state, X^{1}Sigma^{+}, and find that they are exceedingly favourable for laser cooling. We verify that the branching ratio for the spin-forbidden transition to the intermediate a^{3}Pi state is inconsequentially small. We measure the frequency of the lowest rotational transition of the X state, and the hyperfine structure in the relevant levels of both the X and A states, and determine the nuclear electric quadrupole and magnetic dipole coupling constants. Our results show that, with a relatively simple laser cooling scheme, a Zeeman slower and magneto-optical trap can be used to cool, slow and trap BH molecules.